2018
DOI: 10.4172/2161-1122.1000474
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Impact of Zidovudine on Rat Teeth Ontogenesis with Quantitative Laser Induced Fluorescence and an Histomorphological Analysis

Abstract: Azidothymidine is a well-known HIV drug. It is used to treat the early stages of AIDS (Acquired Immune Deficiency Syndrome). Longterm administration of the drug prolongs the life of the infected patient, improves his comfort, and increases the number of lymphocytes. However, it causes severe side effects and is less effective in patients over time. The side effects that may occur as a result of this preparation include anaemia, bone marrow impairment with neutropenia and thrombocytopenia, as well as myopathies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…While crystal structures show that different domain angles can be achieved in different structures (Fig. S1), and both NMR spectros-copy 40,41 and MD simulations have been used to study conformational dynamics in individual POPs, none of the previous MD studies reported spontaneous domain opening or closing during simulations 16,35,[42][43][44][45] . The microsecond MD simulations conducted herein show, for the first time, spontaneous conversion between the open and closed conformations of POP molecules (Fig.…”
Section: Structural Origins Of Pfu Pop Stabilitymentioning
confidence: 99%
“…While crystal structures show that different domain angles can be achieved in different structures (Fig. S1), and both NMR spectros-copy 40,41 and MD simulations have been used to study conformational dynamics in individual POPs, none of the previous MD studies reported spontaneous domain opening or closing during simulations 16,35,[42][43][44][45] . The microsecond MD simulations conducted herein show, for the first time, spontaneous conversion between the open and closed conformations of POP molecules (Fig.…”
Section: Structural Origins Of Pfu Pop Stabilitymentioning
confidence: 99%